Flipped Classroom Combined With Group Awareness - Lin, Jian-Wei; Lin, Hao-Chiang Koong; Hung, Min‑Ling (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
This study proposes a teaching model called “flipped classroom combined with group awareness” (FC+GA) to address the challenge of student preparedness in a traditional flipped classroom (FC) model setting. The FC+GA model incorporates group awareness tools, which provide visual information such as statistical tables and graphs, that allow students to see their online learning status along with that of their peers. By using these tools, students can have a better understanding of how well-prepared they are compared with their peers. This knowledge can motivate them to improve their efforts to prepare before class. The study conducted an extended experiment to analyze the effectiveness of the FC+GA model compared with the traditional FC model. The results show that the FC+GA model significantly improves students’ preparation efforts before class and enhances students’ learning outcomes. The study therefore concludes that the FC+GA model can be used as a practical reference and model for instructors preparing to implement flipped classrooms.